Sosialisasi Gerakan Menabung dan Investasi Di Pasar Modal - Hendrayanti, Silvia; Ernawati, Fidyah Yuli (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
Saving is a wise and strategic step that reflects a person's commitment to financial prosperity and security in the future. In the midst of the dynamics of modern life, saving is not just a habit, but a smart decision that will have a long-term positive impact. Let's explore why saving is so important in laying the foundation for a more stable future. The location of service is at the Semarang College of Economics. The aim of this activity is to provide students with an understanding of the importance of saving, explain the basic concepts and benefits of investing in the capital market and provide practical information about how to start investing in the capital market. The method applied in this activity is to present the material and then make a presentation to the training participants. The service team designs material that can be understood by students. The material is presented clearly and responsively to ensure good understanding. Participants are given the opportunity to discuss and ask questions about the topic of saving and investing in the capital market, thereby ensuring that the information provided can really be applied in everyday life. The service team provides supporting materials in the form of brochures, booklets or small books which can be used as references for participants after the activity ends. The output resulted in an increase in understanding from 11% to 99%. Participants' ability to empower themselves and manage financial literacy optimally is increasing with the knowledge provided in socialization activities.